Analisis Maqasid Syariah Tentang Wakaf Produktif Ekonomi Pesantren - Bung Hijaj Sulthonuddin; Aris Nurrohman (Jurnal Hukum Ekonomi Syariah, 2026)
Productive waqf is one of the instruments of Islamic economics that has great potential in improving the welfare of the ummah. Darussalam Kersamanah Islamic Boarding School, Garut, has developed productive waqf as part of its efforts towards economic independence and empowerment of the surrounding community. The problem is how the mechanism of productive waqf economy of the Islamic Boarding School at Pondok Pesantren Darussalam Kersamanah Garut and how the Analysis of Maqasid Syariah about Productive Waqf in Pondok Pesantren Darussalam Kersamanah Garut. The research method used is a qualitative approach with a case study at Darussalam Kersamanah Islamic Boarding School. Data were collected through observation, in-depth interviews, and document study. The results showed that the management of productive waqf in this pesantren has fulfilled the principles of Maqasid Syariah, namely maintaining religion (hifz ad-din) by strengthening Islamic education, maintaining life (hifz an-nafs) through providing economic needs for students and the community, maintaining reason (hifz al-aql) by increasing access to education, maintaining lineage (hifz an-nasl) by supporting family welfare, and maintaining wealth (hifz al-mal) through optimizing waqf assets for economic sustainability. Productive waqf at Darussalam Kersamanah Islamic Boarding School, Garut, has become a model that can be replicated in the management of pesantren economy based on Maqasid Syariah. Keywords: Maqasid Syariah, Productive Waqf, Pesantren Economy